EXPLORING GREEN CONSUMER BEHAVIOR AND THE EFFECTIVENESS OF GREEN PRODUCT AVAILABILITY IN INTERNATIONAL - CHAIN BUDGET HOTEL IN BEKASI – INDONESIA - Suprapto, Samantha Neno; Haryanto, Jony Oktavian (President University, 2024)
This study investigates the factors influencing green consumer behavior in budget hotels in Indonesia, focusing on the integration of Environmental Concern (EC) and Green Product Availability (GPA) into the Theory of Planned Behavior (TPB) framework. The research examines the relationships between Attitude (ATT), Subjective Norms (SN), Perceived Behavioral Control (PCB), Environmental Concern (EC), Green Intention (GI), Green Consumer Behavior (GCB), and Green Product Availability (GPA) as a moderating variable. Data were collected from 300 respondents through a structured questionnaire and analyzed using SEM-PLS. The findings reveal that ATT, SN, and EC significantly influence GI, with ATT as the strongest predictor. GI is the most significant driver of GCB, confirming its mediating role. However, PCB has limited influence on GCB, highlighting the importance of addressing structural barriers. The moderation analysis shows that GPA significantly strengthens the relationship between GI and GCB, emphasizing the critical role of accessible eco-friendly products in translating intentions into behavior. This study extends the TPB framework and provides practical recommendations for hotel managers and policymakers. Strategies to promote sustainability include fostering positive attitudes, leveraging social norms, and ensuring the availability of green products. Future research should explore additional moderating factors and expand the context to other regions or hotel segments.